Comparative efficacy and safety of high-dose versus low-dose tranexamic acid in adolescent idiopathic scoliosis: A systematic review and meta-analysis - Xin Liu; Zhong Ma; Jiangdong An; Zhiqiang Luo (PLoS ONE, 2025)
Objective The objective of this meta-analysis was to evaluate the comparative effectiveness and safety of high-dose versus low-dose tranexamic acid (TXA) in adolescents undergoing treatment for idiopathic scoliosis. Methods A comprehensive literature search was conducted across PubMed, Web of Science, Embase, Cochrane Library, and China National Knowledge Infrastructure (CNKI) databases up to March 2024. We sought to identify randomized controlled trials (RCTs) and retrospective controlled studies (RCSs) assessing the impact of high-dose compared to low-dose TXA on perioperative blood loss and transfusion requirements in spinal fusion procedures for adolescent idiopathic scoliosis. The study was registered in INPLASY (Registration number: INPLASY202480018). Results Our meta-analysis included data from six studies: two high-quality RCTs and four lower-quality RCSs, comprising a total of 611 participants. Subgroup analysis revealed that high-dose TXA significantly reduced intraoperative blood loss and transfusion rates in RCSs, whereas no significant differences were observed in RCTs. The combined findings showed that high-dose TXA was associated with a significant reduction in intraoperative blood loss [weighted mean difference (WMD) =  -215.48, 95% confidence interval (CI) (-367.58, -63.37), P <  0.001], as well as a decreased likelihood of transfusion [risk ratio (RR) =  0.40, 95% CI (0.30, 0.53), P <  0.001]. Operative time did not differ significantly, and no thromboembolic events were reported in either treatment group. The differences between high and low doses varied widely across studies. Conclusion This meta-analysis indicates that high-dose TXA does not significantly reduce intraoperative blood loss, transfusion rates, or operative time compared to low-dose TXA in adolescent idiopathic scoliosis. While RCSs showed some benefit, our analysis places more emphasis on the results from RCTs, which did not show significant differences. Further high-quality RCTs are needed to confirm its effectiveness and safety.